A 1 year retrospective audit of quality indicators of clinical pharmacological advice for personalized linezolid dosing: one stone for two birds?. (5th December 2015) - Pea, Federico; Cojutti, Piergiorgio; Dose, Lucia; Baraldo, Massimo
Abstract : Aim: This study explored the clinical and economic impact of clinical pharmacological advice (CPA) (based on therapeutic drug monitoring [TDM] results, and on patients' characteristics and co‐medications) on personalized linezolid therapy in a tertiary care hospital. Methods: A 1 year retrospective analysis of quality indicators of CPA (clinicians' adherence rate to CPA, pre‐post rate of linezolid trough concentrations within the desired range and cost balance analysis) was conducted. Results: Five hundred and forty‐four CPAs were provided to clinicians during 2014 for personalizing linezolid therapy in 168 patients. Clinicians' adherence to CPAs was very high (94.7%). The pre‐post rate of linezolid C min distribution showed a favourable impact of CPA on patient care (pre‐post ratio of C min within the desired range + 23.4%, pre, 51.2% vs . post, 74.6%). Overall, linezolid dosage was mainly reduced (56.9% of cases), whereas dose augmentation was needed only in a minority of cases (7.7%). Cost balance analysis showed that overall 1258 standard doses of linezolid (unitary dose 600 mg) were spared for treating 168 patients with a personalized dosage for a median duration of 11 days (range 3–128 days) with a cost saving of 60038.05 €. Conclusion: Active computerized advice elaborated by the clinical pharmacologist on the basis of TDM results and of patient's pathophysiological data and co‐medications may be cost‐effective for personalizing linezolid treatment.